2013
DOI: 10.1890/es13-00118.1
|View full text |Cite
|
Sign up to set email alerts
|

Key landscape ecology metrics for assessing climate change adaptation options: rate of change and patchiness of impacts

Abstract: Abstract. Under a changing climate, devising strategies to help stakeholders adapt to alterations to ecosystems and their services is of utmost importance. In western North America, diminished snowpack and river flows are causing relatively gradual, homogeneous (system-wide) changes in ecosystems and services. In addition, increased climate variability is also accelerating the incidence of abrupt and patchy disturbances such as fires, floods and droughts. This paper posits that two key variables often consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…This situation compares to that of perennial wetlands that contribute species to seasonal wetlands in regions with a Mediterranean climate (Sim et al ., ), and to immigration from source patches that prevents extinction in sink populations (Holyoak, ). The effects of real droughts on the potential resilience of invertebrate communities would thus depend upon the spatial extent of droughts (local or extensive) compared to the spatial scale of our experiment, but also on the patchiness of the disturbance ( sensu Lopez‐Hoffman et al ., ). For instance, drought‐induced tree mortality can be patchy within forests (Breshears et al ., ), resulting in heterogeneous impacts on the understorey environments in terms of evaporation rates, humidity, throughfall upon rewetting, etc.…”
Section: Discussionmentioning
confidence: 97%
“…This situation compares to that of perennial wetlands that contribute species to seasonal wetlands in regions with a Mediterranean climate (Sim et al ., ), and to immigration from source patches that prevents extinction in sink populations (Holyoak, ). The effects of real droughts on the potential resilience of invertebrate communities would thus depend upon the spatial extent of droughts (local or extensive) compared to the spatial scale of our experiment, but also on the patchiness of the disturbance ( sensu Lopez‐Hoffman et al ., ). For instance, drought‐induced tree mortality can be patchy within forests (Breshears et al ., ), resulting in heterogeneous impacts on the understorey environments in terms of evaporation rates, humidity, throughfall upon rewetting, etc.…”
Section: Discussionmentioning
confidence: 97%
“…Steffen et al 2015). Networking within a region also could buffer against impacts of forest die-off , with effectiveness depending on the degree of patchiness (López-Hoffman et al 2013). Collectively, then, many management actions have been identified that could contribute to reducing forest vulnerability to hotter drought.…”
Section: Mechanisms (Mc)mentioning
confidence: 99%
“…In others, no such division was apparent (Ganey and Vojta 2011). These results translate to considerable uncertainty in forecasting when and where forest mortality would occur within the landscape in future drought events, which greatly constrains management options , Lo´pez-Hoffman et al 2013; see Discussion: Implications to forest resilience following drought).…”
Section: Patchy Spatially Variable Density-independent Mortality; Pmentioning
confidence: 99%